Suicide rates among people with serious mental illness: a systematic review and meta-analysis. Issue 2 (6th January 2023) - Fu, Xue-Lei; Qian, Yan; Jin, Xiao-Hong; Yu, Hai-Rong; Wu, Hua; Du, Lin; Chen, Hong-Lin; Shi, Ya-Qin
Abstract: Background: People with serious mental illness are at great risk of suicide, but little is known about the suicide rates among this population. We aimed to quantify the suicide rates among people with serious mental illness (bipolar disorder, major depression, or schizophrenia). Methods: PubMed and Web of Science were searched to identify studies published from 1 January 1975 to 10 December 2020. We assessed English-language studies for the suicide rates among people with serious mental illness. Random-effects meta-analysis was used. Changes in follow-up time and the suicide rates were presented by a locally weighted scatter-plot smoothing (LOESS) curve. Suicide rate ratio was estimated for assessments of difference in suicide rate by sex. Results: Of 5014 identified studies, 41 were included in this analysis. The pooled suicide rate was 312.8 per 100 000 person-years (95% CI 230.3–406.8). Europe was reported to have the highest pooled suicide rate of 335.2 per 100 000 person-years (95% CI 261.5–417.6). Major depression had the highest suicide rate of 534.3 per 100 000 person-years (95% CI 30.4–1448.7). There is a downward trend in suicide rate estimates over follow-up time. Excess risk of suicide in males was found [1.90 (95% CI 1.60–2.25)]. The most common suicide method was poisoning [21.9 per 100 000 person-years (95% CI 3.7–50.4)]. Conclusions: The suicide rates among people with serious mental illness were high, highlighting the requirements for increasing psychological assessment and monitoring. Further study should focus on region and age differences in suicide among this population.